Perilaku Penggunaan Daun Seurapoh Dalam Pencegahan Penyakit Menular Melalui kontaminasi luka Pada Keluarga Pasca Bencana Gempa Tsunami Di Banda Aceh: Lesson Learn Pasca Bencana Aceh Tahun 2004 - Cipta, Hendra (Pusat Studi Wanita UIN Ar-Raniry, 2024)
The post disaster of tsunami-earthquake on December 26, 2004 and predicted severe conditions such epidemic but not proven, it's an interesting thing to study. The study aims to explore the behavior of the family of Banda Aceh faces outbreaks diseases through the contamination of the wound so as to prevent an outbreak of post disaster. Exploratory qualitative research with data sources from the family and key persons. Data was collected through interviews in the three districts of Banda Aceh on the different categories of disasters. The results of the study there was a positive family behavior in the prevention of infectious diseases outbreak the disaster. The study concluded the presence of behavioral local wisdom of the family in the prevention of infectious diseases through wound contamination in the form of caring for his own adapted to the availability of remedy or medicine, wiping the wound with clean water or heated, close the wound with a clean cloth, went to officer / places health services. Suggestions in this study; as learning to be applied other countries as well as necessary to prove the use of leaf Seurapoh wound care family for medicinal.